2022
DOI: 10.3390/jpm12091449
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins G of Patients with Schizophrenia Protects from Superoxide: Pilot Results

Abstract: This study aimed to evaluate the superoxide dismutase (SOD) activity of IgG in patients with schizophrenia. After signing informed consent, we included 67 patients with schizophrenia (34 people with acute schizophrenia and 33 individuals were on outpatient treatment in therapeutic remission) and 14 healthy volunteers. IgGs from blood serum were isolated by affinity chromatography. SOD activity of antibodies was determined spectrophotometrically. We have shown for the first time that IgGs from patients with sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…SOD activity of IgG was expressed in the following units: the difference in optical density between the spontaneous and induced reaction proceeding for 1 min in terms of mg of IgG (µM diformazan/min/mg IgG) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD activity of IgG was expressed in the following units: the difference in optical density between the spontaneous and induced reaction proceeding for 1 min in terms of mg of IgG (µM diformazan/min/mg IgG) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…IgG SOD activity has been found in schizophrenia and multiple sclerosis, but the function of abzymes having antioxidant activity is not fully understood. Over the past few years, abzymes with nuclease [ 17 , 18 ], proteolytic [ 19 , 20 ], catalase [ 21 ], and superoxide dismutase (SOD) activities [ 22 ] have been found in the blood serum of patients with schizophrenia. One hypothesis about the pathogenesis suggests that catalytic antibodies with catalase and SOD activities help protect the body from excessive concentrations of reactive oxygen species (ROS) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, group of the researchers at the Mental Health Research Institute of Tomsk National Research Medical Center of the Russian Academy of Sciences (Tomsk, Russia) in collaboration with The Institute of Chemical Biology and Fundamental Medicine of Siberian Division of Russian Academy of Sciences (Novosibirsk, Russia) has investigated a number of catalytic activities of immunoglobulins G in patients with schizophrenia. They reported that abzymes isolated from the blood serum of patients exhibited catalase activity ( Ermakov et al, 2017 ), superoxide dismutase activity ( Mednova et al, 2022 ), nuclease activity ( Ermakov et al, 2015 ; Ermakov et al, 2018 ) and proteolytic activity to MBP ( Parshukova et al, 2020b ; Parshukova et al, 2019 ), histones ( Ermakov et al, 2020 ), and collagen ( Parshukova et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%